2009
DOI: 10.1089/end.2008.0650
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral Lubricants: A Critical Literature Review and Recommendations

Abstract: In current clinical practice, lidocaine gel is widely used as a local anesthetic lubricant before various forms of transurethral instrumentation. Over the past few years, the value of local anesthesia during urethral catheterization and flexible or rigid cystoscopy has been questioned. Strong data are lacking, and the results from the different studies are contradictory. As a result, the correct use of the intraurethral gels is, for the most part, left to individual preference. The purpose of this review is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
0
15
0
12
Order By: Relevance
“…1 Tzortzis et al in review of literature observed that intraurethral anesthetic jelly dwell time of 10-20 minutes is optimum for pain relief in men undergoing rigid cystoscopy. 10 Literature review on the effectiveness of local anesthetic jelly for pain relief during male flexible cystoscopy shows conflicting results. Patel et al, in their meta-analysis, reported on 817 patients from nine eligible trials.…”
Section: Discussionmentioning
confidence: 99%
“…1 Tzortzis et al in review of literature observed that intraurethral anesthetic jelly dwell time of 10-20 minutes is optimum for pain relief in men undergoing rigid cystoscopy. 10 Literature review on the effectiveness of local anesthetic jelly for pain relief during male flexible cystoscopy shows conflicting results. Patel et al, in their meta-analysis, reported on 817 patients from nine eligible trials.…”
Section: Discussionmentioning
confidence: 99%
“…The chlorhexidine gel is widely used for this procedure. 21 However, there are no studies of the effects of lubricants on the recurrence of urethral stricture. Future studies should look at the impact of different lubricants on the recurrence of urethral stricture after EIU.…”
Section: Discussionmentioning
confidence: 99%
“…Araştırmacıların çoğunun bireysel tercihler yapmış olması, çalışma sonuçlarında bildirilen etki konusunda ciddi bir veri eksikliğinin olması bu konunun çık-mazlarıdır. Bu nedenle ağrısız transüretral uygulamalar için genel anestezi tercih nedeni olmuştur [14]. Genel anestezinin maliyeti, riskleri ve oldukça zaman alan hazırlık döneminden dolayı, klinik uygulamada daha pratik olan üretral yoldan lokal anestezik verilerek işlem yapılması gündeme gelmiştir.…”
Section: Discussionunclassified